Anti‐IL‐5 attenuates activation and surface density of β2‐integrins on circulating eosinophils after segmental antigen challenge. Issue 3 (17th February 2013) - Johansson, M. W.; Gunderson, K. A.; Kelly, E. A. B.; Denlinger, L. C.; Jarjour, N. N.; Mosher, D. F.
Summary: Background: IL‐5 activates αM β2 integrin on blood eosinophils in vitro . Eosinophils in bronchoalveolar lavage (BAL) following segmental antigen challenge have activated β2 ‐integrins. Objective: To identify roles for IL‐5 in regulating human eosinophil integrins in vivo . Methods: Blood and BAL eosinophils were analysed by flow cytometry in ten subjects with allergic asthma who underwent a segmental antigen challenge protocol before and after anti‐IL‐5 administration. Results: Blood eosinophil reactivity with monoclonal antibody (mAb) KIM‐127, which recognizes partially activated β2 ‐integrins, was decreased after anti‐IL‐5. Before anti‐IL‐5, surface densities of blood eosinophil β2, αM and αL integrin subunits increased modestly post challenge. After anti‐IL‐5, such increases did not occur. Before or after anti‐IL‐5, surface densities of β2, αM, αL and αD and reactivity with KIM‐127 and mAb CBRM1/5, which recognizes high‐activity αM β2, were similarly high on BAL eosinophils 48 h post‐challenge. Density and activation state of β1 ‐integrins on blood and BAL eosinophils were not impacted by anti‐IL‐5, even though anti‐IL‐5 ablated a modest post‐challenge increase on blood or BAL eosinophils of P‐selectin glycoprotein ligand‐1 (PSGL‐1), a receptor for P‐selectin that causes activation of β1 ‐integrins. Forward scatter of blood eosinophils post‐challenge was less heterogeneous and on the average decreased after anti‐IL‐5; however, anti‐IL‐5 had no effect on the decreased forward scatter of eosinophils in post‐challenge BAL compared with eosinophils in blood. Blood eosinophil KIM‐127 reactivity at the time of challenge correlated with the percentage of eosinophils in BAL post‐challenge. Conclusion and Clinical Relevance: IL‐5 supports a heterogeneous population of circulating eosinophils with partially activated β2 ‐integrins and is responsible for up‐regulation of β2 ‐integrins and PSGL‐1 on circulating eosinophils following segmental antigen challenge but has minimal effects on properties of eosinophils in BAL. Dampening of β2 ‐integrin function of eosinophils in transit to inflamed airway may contribute to the decrease in lung inflammation caused by anti‐IL‐5.